2018
DOI: 10.32385/rpmgf.v34i2.12399
|View full text |Cite
|
Sign up to set email alerts
|

Terapêutica crónica em idosos numa Unidade de Saúde Familiar: análise da polimedicação e medicação potencialmente inapropriada

Abstract: de medicina geral e familiar. USF Manuel Rocha Peixoto-Braga. INTRODUÇÃO O envelhecimento da população O aumento da esperança média de vida em Portugal, nas últimas décadas, coloca um dos principais desafios do nosso século que será satisfazer a maior procura de cuidados de saúde, adaptá-los a esta nova realidade e mantê-los económica e socialmente viáveis numa sociedade reflexamente com menos população ativa. 1-4 O envelhecimento da população é um fenómeno global. Prevê-se que os 11% de população com idade su

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 19 publications
4
5
0
1
Order By: Relevance
“…The majority of respondents (95,0%) lived in the municipality of Valpaços (Table 1). The distribution by gender shows a predominance of females (53,3%), data corroborated by other studies (Cima, et al, 2011;Soares et al, 2011;Souto & Pimentel, 2018) and corresponding to the expected, since in Portugal the longevity of females is higher than the male, although less healthy (INE, 2018;SNS, 2017). It was found that 55,0% of the interviewees were married and 28,3% were widowed, and 71,7% lived accompanied, as well as the results of Monterroso et al (2015) and Souto & Pimentel (2018).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The majority of respondents (95,0%) lived in the municipality of Valpaços (Table 1). The distribution by gender shows a predominance of females (53,3%), data corroborated by other studies (Cima, et al, 2011;Soares et al, 2011;Souto & Pimentel, 2018) and corresponding to the expected, since in Portugal the longevity of females is higher than the male, although less healthy (INE, 2018;SNS, 2017). It was found that 55,0% of the interviewees were married and 28,3% were widowed, and 71,7% lived accompanied, as well as the results of Monterroso et al (2015) and Souto & Pimentel (2018).…”
Section: Resultssupporting
confidence: 85%
“…The distribution by gender shows a predominance of females (53,3%), data corroborated by other studies (Cima, et al, 2011;Soares et al, 2011;Souto & Pimentel, 2018) and corresponding to the expected, since in Portugal the longevity of females is higher than the male, although less healthy (INE, 2018;SNS, 2017). It was found that 55,0% of the interviewees were married and 28,3% were widowed, and 71,7% lived accompanied, as well as the results of Monterroso et al (2015) and Souto & Pimentel (2018). More than a quarter of respondents (26,7%) had completed primary school, which matches with other studies carried out previously in the same age group (Cima et al, 2011;Serrão et al, 2015).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…A realização deste estudo permitiu caracterizar a realidade da polimedicação do utente muito idoso na USF em estudo, potenciando a consciencialização indivi-dual e da equipa para esta problemática. A prevalência de doentes polimedicados encontrada foi superior à relatada noutros estudos realizados em contexto de cuidados de saúde primários, [7][8] estudosoriginais Castilho e colaboradores, que revelou uma frequência de polifarmácia na amostra de utentes com idade igual ou superior a 75 anos de 62,3%. 9 Todos os médicos de família sobrestimaram a percentagem de utentes da sua lista medicados com benzodiazepinas.…”
Section: Estudosoriginais Discussão/conclusãounclassified